KERAGAMAN AVIFAUNA DI KAWASAN AGROWISATA SALAK SIBETAN KARANGASEM - Kaler Surata, Sang Putu (Bumi Lestari; Vol 5 No 1)
Survey concerning bird which involved species richness and abundances have beencarried out in Sibetan Agrotourism , Karangasem, between January and August 2004. Datawere collected utilizing line transects, free exploration,and point count techniques as wellas by interviewing the local resident. From 43 bird species that have been identified, morethan 80 percent had interesting appearances, voice, and behavior. Nine species,( GreenJungle Fowl, Yellow-vented Bulbul, Black-naped Oriole, Magpie Robin, Sooty-headedBulbul, Bar-winged Prinia, Peaceful Dove Orange-headed Thrush, and Spotted Dov), areconsidered to be atractive bird, because of their body beauty, mobility behavior as well as byinteresting call. These are very potential to give added values to Agrotourism of Sibetan.For these purposes, improvement community’s corcern ,rehabilitation of habitat, captivebreeding, and reintroduction of threatened species from locality extinction are needed
Keywords: species richness, species abundances, exotic birds, and added value